ANALISIS PENGARUH PEMBIAYAAN MURABAHAH DAN MUDHARABAH TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING - SLAMET RAHARJO; SALAMAH WAHYUNI (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2019)
The purpose of this study was to analyze the effect of murabahah and mudharabah on the value of the Islamic Sharia Bank with profitability as an intervening variable. The data used in this study were obtained from several sources of activity (field) to obtain financial reports in Sharia Commercial Banks in Indonesia in 2013-2017. Data analysis in this study used path analysis. The results showed that murabaha and mudharabah had a significant effect on profitability and mudharabah with profitability had an effect on the firm value of Islamic Commercial Banks in Indonesia. The results of this study also show that murabaha and mudharabah influence the value of the company with profitability as an intervening variable. Keywords: Murabahah, Mudharabah, Profitability, Corporate Value